In Vitro evaluation of the anti-pancreatic cancer activity of epimedium herb - Chen, Yangfeng; Xia, Han; Zhong, Xiaohong (Frontiers in Pharmacology, 2024)
The active components, potential targets, and mechanisms of epimedium action in treating pancreatic cancer (PC) were investigated using network pharmacology, molecular docking, and in vitro validation. HPLC was used to determine the active ingredient content of epimedium, and HPLC-Q-TOF-MS was utilized for qualitative identification. The potential targets of the active ingredients in epimedium were screened from TCMSP, ETCM, CTD Database, and Swiss Target Prediction. Subsequently, DisGeNET, GeneCards, and OMIM databases were explored for potential PC-related targets. PPI network analysis, GO, and Reactome pathway enrichment analyses were conducted to assess epimedium's core targets and pathways against PC. Additionally, molecular docking was utilized to examine the interactions between active compounds and these core targets. The expressions of significantly predicted target genes in normal tissues relative to PC tissues and their correlation with the overall survival of PC patients were analyzed using GEPIA2 and HPA databases. In vitro assays confirmed that epimedium extract (EPE) markedly diminished the cellular viability of Panc-1 cells. Western blot analysis established that the expression of key targets, including AKT1, EGFR, p-EGFR, JUN, BCL2, IL6, and SRC, was considerably lowered in EPE-treated Panc-1 cells. Epimedium, containing baohuoside I, icariin, hyperoside, and epimedin B as its main active components, has been suggested to possess therapeutic potential against PC. Epimedium may inhibit tumor growth through the R-HSA-1280215: Interleu in-4 and Interleukin-13 signaling, involving AKT1, EGFR, JUN, BCL2, IL6, and SRC genes. These findings suggest that epimedium may serve as a promising subsequent treatment for PC and warrant further exploration.